Associations of ADHD traits, sleep/circadian factors, depression and quality of life - Catherine Hill; Samuele Cortese; Eus J W Van Someren; Sarah Laxhmi Chellappa; Siddhi Nair; Neha Deshpande (BMJ Mental Health)
Background Individuals with attention deficit hyperactivity disorder (ADHD) are at a higher risk of depression and lower quality of life (QoL); however, it is unclear whether disrupted sleep and circadian rhythms mediate this increased risk.Objectives We investigated whether disruption of self-reported sleep and circadian factors mediate the associations of ADHD traits with depression symptom severity and QoL.Methods 1364 participants (mean: 51.86 (SD=0.37) years, 75% women) from a large-scale cross-sectional online survey (Netherlands Sleep Registry) completed a sociodemographic questionnaire, the Adult ADHD Rating Scale, Hospital Anxiety and Depression Scale, Satisfaction With Life Scale (SLS) and Cantril Ladder (CL) (QoL measures), Insomnia Severity Index, Pittsburgh Sleep Quality Index and Munich Chronotype Questionnaire.Findings Higher ADHD traits were significantly associated with depression symptom severity (p=0.03), lower QoL (p<0.001), insomnia severity (p<0.001), lower sleep quality (p<0.001) and later chronotype (p=0.01). No sleep or circadian factor significantly mediated the association of the severity of symptoms of ADHD and depression (all p>0.1). Conversely, only insomnia severity significantly mediated the association of ADHD traits and QoL (SLS: standardised β=−0.10, 95% CI (−0.12 to –0.04); CL: standardised β=0.103, 95% CI (0.04 to 0.16)).Conclusion ADHD traits were associated with lower QoL and it was partially mediated by insomnia severity. Future studies targeting insomnia complaints in this population may help mitigate their depression complaints and improve their QoL.Clinical implications Our results may help current clinical guidelines that do not typically link sleep/circadian complaints to QoL in ADHD assessment.